Exploring code-switching and code-mixing dynamics in Sundanese-Indonesian bilingual aphasia - Nasrullah, Riki; Lukman, Fahmy; Parmin, Parmin (LITERA, 2023)
This research explores the intricate phenomenon of code-switching and code-mixing within the realm of bilingual aphasia patients who converse in both Sundanese and Indonesian. This research is essential to understanding the code-switching and code-mixing phenomenon to improve rehabilitation and effective communication for these patients. Employing a descriptive-qualitative methodology, this study aims to shed light on the language dynamics exhibited by these individuals. To this end, data were meticulously gathered through participant observation in everyday communication, supplemented by in-depth interviews conducted with family members and language therapists. The findings from meticulous data analysis illuminate that aphasia patients fluently alternate between Sundanese and Indonesian, frequently engaging in code-switching and code-mixing when grappling with linguistic expression or comprehension difficulties. Furthermore, this language phenomenon manifests in the patients' inclination toward employing shorter and simpler sentence structures. Consequently, these results underscore the importance of accounting for language selection, code-switching, and code-mixing within the language therapy process for Sundanese-Indonesian bilingual aphasia patients. Language therapists are urged to comprehend and adapt to the patients' flexible language utilization while devising tailored therapeutic strategies to enhance their linguistic proficiency. Moreover, this research calls for future investigations to explore this captivating phenomenon across diverse cohorts of bilingual aphasia patients, thus broadening our understanding of the intricacies involved.